Mutator mutations in bacteriophage T4 gene 32 (DNA unwinding protein). - Koch, R E (1976)
Bacteriophage T4 gene 32 encodes a DNA unwinding protein required for DNA replication, repair, and recombination. Gene 32 temperature-sensitive mutations enhance virtually all base pair substitution mutation rates.